Помогите срочно!

Найдите значение выражения:

m - 6n^2 2n
------------ + 3n - --------- если m=12, n= -3
2n - 1 1 - 2n

2

Ответы и объяснения

  • Участник Знаний
2014-03-05T06:49:11+04:00
(m-6n²)/(2n-1)+3n+2n/(2n-1)=(m-6n²+6n²-3n+2n)/(2n-1)=(m-n)/(2n-1)=
=(12+3)/(-6-1)=-15/7=-2 1/7
2014-03-05T07:19:05+04:00
 \frac{m-6 n^{2} }{2n-1} + 3n -  \frac{2n}{1-2n} =   \frac{m-6 n^{2} }{2n-1} +3n +   \frac{2n}{2n-1} =   \frac{m-6 n^{2}+3n(2n-1)+2n}{2n-1}  = 

=  \frac{m-6 n^{2}+6 n^{2}-3n+2n}{2n-1}  =    \frac{m-n }{2n-1}  

если m=12, n= -3, то

   \frac{m-n }{2n-1}  =    \frac{12-(-3)}{2(-3)-1} =   \frac{12+3}{-6-1} = -   \frac{15}{7} = -2  \frac{1}{7}